Post‐discharge neonatal hyperbilirubinemia surveillance. (6th December 2019) - Kaplan, Michael; Zimmerman, Deena; Shoob, Hanna; Stein‐Zamir, Chen
Abstract: Aim: To assess implementation of the Israel Neonatal Society's 2008 guidelines for universal community assessment of jaundice within 72 hours of discharge from birth hospitalisation. Methods: Mothers of newborns were interviewed at Maternal Child Health Clinics in the Jerusalem District, Israel, and asked whether their newborn had been evaluated for jaundice within the recommended time frame. Newborn discharge letters from Israeli hospitals were assessed for appropriate inclusion of instructions for early follow‐up for jaundice. Results: Out of 659, 217 (32.9%) mothers whose newborns were at low risk for neonatal hyperbilirubinemia reported an examination within 72 hours of discharge. Eighteen (8.3%) were referred for a bilirubin test. In contrast, 99.1% (109/110) of high‐risk newborns who were specifically invited for a bilirubin test the day following discharge complied. Out of 26, 12 (46.2%) hospital discharge letters specified both a time limit of 72 hours post‐discharge and jaundice as a reason for early follow‐up. Conclusion: The early community surveillance rate for jaundice was low, contrasting with near universal compliance in those who received a specific instruction for a post‐discharge bilirubin blood test. Inclusion of specific written instructions in hospital discharge summaries was also low and may contribute to poor implementation of guidelines. Abstract :